Intercultural communication experiences of foreign students with a focus on their perspectives of national, cultural and ethnic identity : case of exchange and degree students in Jyväskylä, Finland - Natarova, Tatiana (2011)
The aim of the study is to learn about intercultural communication experiences of foreign Exchange and Master degree students in Jyväskylä, Finland with a particular attention to the perspective of national, cultural and ethnic identity concepts.